Structure and Composition of Vegetation at Parak Ecosystem in Nagari Lubuk Pandan District 2X11 Enam Lingkung Padang Pariaman Regency - Fadhlurrohman, Reza; Anhar, Azwir; Kardiman, Reki; Eka Putri, Irma Leilani (Jurnal Serambi Biologi, 2023)
Parak is the most common agroforestry site, especially on dry land in the form of gardens or fields. The term parak is only used by people in West Sumatra, and is a release of the ecosystem between agricultural land and forests. Parak has many different species, with many trees, and a complex and layered vertical structure. The purpose of this study was to determine the structure and composition of vegetation in the Parak ecosystem in Nagari Lubuk Pandan, 2X11 Enam Lingkung District, Padang Pariaman Regency, West Sumatera. The method used is a field survey method by making observation plots measuring 10m x 10m for trees and sub-plots 5m x 5m for poles, 2m x 2m for undergrowth placed in the parak area in Nagari Lubuk Pandan District 2X11 Enam Lingkung, Padang Pariaman Regency, West Sumatera. The results of this study obtained the highest INP value, namely the type Durio zibethinus L. with an INP value of 32.57. The index value of hostility in the parak ecosystem in Nagari Lubuk Pandan is high and community stability is high with a diversity index of 3.50. The composition of plant species in the parak ecosystem consists of 61 plant species with 35 different families.